Find the sum of 100 terms of the series
1^2 -2^2 + 3^2- 4^2 + 5^2 -6^2......... +99^2 -100^2 ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
the series is 1, -3, 6, -10, 15, -21, 28, 36, -45 The sequence is of triangular numbers given by n(n+1)/2 where n is the nth term of series n=100. 100*101/2= 5050 finally every even term will yield negative value so -5050
1 2 − 2 2 + 3 2 − 4 2 + . . . + 9 9 2 − 1 0 0 2 =
( 1 − 2 ) ( 1 + 2 ) + ( 3 − 4 ) ( 3 + 4 ) + . . . + ( 9 9 − 1 0 0 ) ( 9 9 + 1 0 0 ) = Difference of squares
( − 1 ) ( 1 + 2 ) + ( − 1 ) ( 3 + 4 ) + . . . + ( − 1 ) ( 9 9 + 1 0 0 ) =
− ( 1 + 2 + 3 + 4 + . . . + 9 9 + 1 0 0 ) = Factor out -1
− 2 1 0 0 ( 1 + 1 0 0 ) = Arithmetic sum formula
− 5 0 ( 1 0 1 ) =
− 5 0 5 0
sum(1^2+2^2+3^2+...+n^2)= n (n+1) (2n+1)/6 (>>>this is a well known fact) So, here, the series is: 1^2-2^2+3^2+...+99^2-100^2 which can be broken into: (1^2+2^2+3^2+...+100^2) - 2 * (2^2+4^2+6^2+...+100^2) =(1^2+2^2+3^2+...+100^2) - 2 * 4 * (1^2+2^2+3^2+...+50^2) (>>>taking out 2^2 common from second bracket) =(100 * 101 * 201)/6 - (8 * 50 * 51 * 101)/6 =50 * 101 * (67-68) (>>>simplification, after geting common factors from both fractions) = (-5050), that is the answer :)
DISCLAIMER : This is a whatever-gets-the-job-done approach. As I am not really into technical (for the lack of a good term) mathematics, what I offer here is a long roundabout method. There definitely are shorter solutions than this one. I am only sharing how I found the answer.
The numbers' squares proceed as
1 , 4 , 9 , 1 6 , 2 5 , …
The differences of all ( i + 1 ) 2 − i 2 form the sequence of odd numbers:
1 = 1 = n 1
3 = 4 − 1 = n 2 − n 1
5 = 9 − 4 = n 3 − n 2
7 = 1 6 − 9 = n 4 − n 3
9 = 2 5 − 1 6 = n 5 − n 4 …
and the sequence can be thought of as
1 , ( 1 2 + 3 ) , ( 2 2 + 5 ) , ( 3 2 + 7 ) , ( 4 2 + 9 ) , …
Take 5 2 . 5 2 is the sum of 4 2 and 9 . But 4 2 = 3 2 + 7 , 3 2 = 2 2 + 5 , and 2 2 = 1 2 + 3 . The same thing can be said for all n 2 . Thus, the recent sequence above can be rewritten as
1 , ( 1 + 3 ) , ( 1 + 3 + 5 ) , ( 1 + 3 + 5 + 7 ) , ( 1 + 3 + 5 + 7 + 9 ) , …
Now, we consider the given problem but I will now state it as:
1 − ( 1 + 3 ) + ( 1 + 3 + 5 ) − ( 1 + 3 + 5 + 7 ) + ( 1 + 3 + 5 + 7 + 9 ) − …
For instance, we have the sequence until 6 2 . If the numbers are regrouped and added, we get
1 − ( 1 + 3 ) + ( 1 + 3 + 5 ) − ( 1 + 3 + 5 + 7 ) + ( 1 + 3 + 5 + 7 + 9 ) − ( 1 + 3 + 5 + 7 + 9 + 1 1 )
= 1 − ( 1 ) − 3 + ( 1 + 3 + 5 ) − ( 1 + 3 + 5 ) − 7 + ( 1 + 3 + 5 + 7 + 9 ) − ( 1 + 3 + 5 + 7 + 9 ) + 1 1
= 3 + 7 + 1 1
If we only considered the sum up to 2 2 , we only have 3 . If up to 4 2 , we have 3 + 7 . For up to 6 2 , as we saw just above, the sum is 3 + 7 + 1 1 . We have the sum of a sequence of numbers with a 1 = 3 and a i + 1 − a i = d = 4 . With the original question having terms up to 1 0 0 2 , we can regroup the sequence as fifty pairs of ( n + 1 ) 2 − n 2 . The sum of this sequence is
S n = 2 n ( 2 a 1 + ( n − 1 ) ( d ) ) = 2 5 0 ( 2 ( 3 ) + ( 5 0 − 1 ) ( 4 ) ) = 5 0 5 0 .
Problem Loading...
Note Loading...
Set Loading...
1^2 - 2^2 + 3^2 - 4^2 .......... - 100^2
1 - 4 + 9 - 16 + 25 -36.. ... ... .... .... - 100^2
-3 + -7 + -11..... ............
so we get aritmathic problem n = 50 because we allready use 2 to make arithmathic
so, SUM = n/2 (2a + (n-1)b) a = first term b= gap beetwen first term and second term
SUm = 50/2 (2(-3) + (50-1) -4) = 25 ( -6 + -196) = 25 ( -202) = -5050